Insights into ThB40: Stability, Electronic Structure, and Interaction - Yutian Li; Yingying Wang; Zhanrong Zhou; Yang Gao; Yiming Chen; Guoqing Zhang; Chao Ma (Molecules, 2024)
The interaction between nonmetal and metal atoms has attracted great interest in the development of organometallic compounds and their promising applications. In this study, we explored the interaction between boron and thorium atoms, based on the stable B40Th coordination compound, by employing density functional theory calculations. We elucidated the stability and geometries of the B40Th coordination compound and revealed the electron transfer from the metal atom Th to B40, which is evidenced by the natural bond orbital calculations. This electron transfer is attributed to the electron-withdrawing character of the boron atom and results in clear electrostatic interaction. Additionally, bond critical analysis and bond order calculations show obvious covalent characters between the metal and nonmetal atoms. The IR spectrum was simulated to give detailed information to identify this targeted compound in future experiments. This study is expected to enhance the understanding of metal–nonmetal interactions and provides useful information for constructing new organometallic compounds based on actinium metal atoms.